Tribological Characterization of Epoxy Hybrid Composites Reinforced with Al2O3 Nanofiller - K. Dilip Kumar; M. Shantharaja; M. D. Kiran; M. Rajesh; Nithin Kumar; Haiter Lenin (Advances in Materials Science and Engineering)
The addition of fillers to polymer composites induces a positive influence on the mechanical and tribological properties of the hybrid composites. These properties can be validated for possible uses such as automobile, construction, shipping, aerospace, sports equipment, electronics, and biomedical domains. In the present research, epoxy matrix reinforced with nylon-6 fibers and glass fibers were prepared using the solution blend technique. Alumina nanoparticles are added as fillers to enhance the properties of epoxy hybrid composites. The large surface area of interaction of nanofillers exhibits better adhesion between matrix and fibers of composites, and it significantly affects the various properties of composites. The tribological characteristics of fabricated epoxy hybrid composites were evaluated under various parameters and conditions. The results revealed that the addition of nanofiller significantly reduces the wear loss of epoxy hybrid nanocomposites. The wear resistance of epoxy hybrid composites increased with increase in addition of nanofiller up to 1.0%, and it slightly decreased with the further addition of filler. The Taguchi analysis was carried out for the least coefficient of friction and specific wear rate. The analysis found that the specific wear rate and coefficient of friction mainly depend on load, followed by speed and nanofiller. The fractured and worn surface of Al2O3-filled epoxy hybrid composites was analysed using SEM.